The Effectiveness of the Office of Women’s Empowerment, Child Protection, and Family Planning (DP3AKB) Program in Reducing the Incidence of Violence Against Women and Children in West Java Province (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to evaluate the effectiveness of programs implemented by the Office of Women’s Empowerment, Child Protection, and Family Planning (DP3AKB) of West Java Province in reducing violence against women and children. The research adopts a qualitative approach through an exploratory case study design to obtain an in-depth understanding of policy implementation and program outcomes. Data were collected through in-depth interviews with key stakeholders, participatory observation, and systematic document analysis. The findings indicate that although protection policies have been formally formulated and supported by regulatory frameworks, their implementation still faces significant challenges. These challenges include limited human resources, inadequate technical capacity, suboptimal inter-agency coordination, and persistent cultural resistance rooted in patriarchal norms within communities. Nevertheless, several flagship programs, such as Sekoper Cinta, UPTD PPA, and PUSPAGA, have demonstrated positive impacts, particularly in improving victim identification, handling, referral mechanisms, and psychosocial recovery services. Overall, the study concludes that the effectiveness of protection programs depends heavily on strong cross-sectoral integration, sufficient and sustainable budgetary support, and active community participation. Therefore, the study recommends strengthening data-driven monitoring and evaluation systems, expanding capacity-building and training for officers and community volunteers, and institutionalizing the human security approach into regional development planning.